AMS method validation for quantitation in pharmacokinetic studies with concomitant extravascular and intravenous administration. (February 2011) - Lappin, Graham; Seymour, Mark; Young, Graeme; Higton, David; Hill, Howard M
A technique has emerged in the past few years that has enabled a drug''s intravenous pharmacokinetics to be readily obtained in humans without having to conduct extensive toxicology studies by this route of administration or expend protracted effort in formulation. The technique involves the intravenous administration of a low dose of 14 C-labelled drug (termed a tracer dose) concomitantly with a non-labelled extravascular dose given at therapeutically levels. Plasma samples collected over time are analysed to determine the total parent drug concentration by LC––MS (which essentially measures that arising from the oral dose) and by LC followed by accelerator mass spectrometry (AMS) to determine the 14 C-drug concentration (i.e., that arising from the intravenous dose). There are currently no published accounts of how the principles of bioanalytical validation might be applied to intravenous studies using AMS as an analytical technique. The authors describe the primary elements of AMS when used with LC seperation and how this off-line technique differs from LC––MS. They then discuss how the principles of bioanalytical validation might be applied to determine selectivity, accuracy, precision and stability of methods involving LC followed by AMS analysis.